Legal Paradigm Shifting Rural Credit Bank of Indonesia (BPR) to Enhance Indonesia Banking in the Global Market: A Normative Legal Study - Ningsih, Ayup Suran; Fidiyani, Rini; Haryakusuma, Adil Putra; Nion, Norhaini Binti; Wardhani, Harumsari Puspa (Journal of Law and Legal Reform, 2026)
The development of regulations resulting from the Financial Sector Development and Strengthening Act (P2SK Act) has changed the acronym of the People’s Credit Bank to the People’s Economic Bank, which, of course, changes the needs of today’s society. This research also aims to analyze the extent to which the government adapts to technological and informatics developments through progressive regulatory updates as evidenced by the emergence of new financial regulations, namely the P2SK Law. The research method used in this study is a comparative approach that analyzes the comparison of credit lending institutions before and after the P2SK Law. The analysis applied in this research is the Qualitative Method of Comparative Analysis Model, which compares two objects under study based on the author’s framework of thought. This normative-empirical legal research is studied based on regulations and examined based on social empirical facts in the field. The data processed comes from literature studies of previous studies collected and analyzed by the author. The results of this study interpret that the monetary and real sectors are integrated with regulations created by the government, which are mutually compatible. Regulatory updates must also follow the rapid development of the times in the economic sector, which is the main factor supporting the prosperity of a country. The substance of the new regulations of the P2SK Law is also adjusted to the needs of the community through the functions and principles of the People’s Economic Bank itself.